Innovative Strategies in the Classroom: An Experience - Sonwane , Prof. J. R. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Learning outcome isn‘t a process of result in the form of marks to declare pass or fail, but a statement which shows what the learner did the learning; what is known or what they able to do? Here, it is a matter of measurable skills, knowledge or capability that students can present at the end of the course. Therefore, it is very necessary that it should be realistic and time bound. To get such outcome, the teacher has to make special plans, which will help in getting the desired result. Keep these things in focus, in this paper, I have discussed the various learning techniques used by me in my classroom to get better learning outcome like, jigsaw learning classroom, problem-based learning and the muddiest point technique. In this experiment, 34 students studying Master of Education at Department of Education, M. K. Bhavnagar University, and Gujarat were included as a sample. In this paper, three things have been put in the centre: First, the techniques used by me in the classroom. Secondly, my observation of the use of the exercises and third one is, the opinion of the experience of students learning through these experiments. An attempt has been made to find out the result by qualitative analysis of the information.